Kecerdasan Emosi dan Kecerdasan Kalbu dengan Pendekatan Tasawuf: Mewujudkan Keberagamaan yang Moderat - Rahayu, Endang Sri (Asosiasi Dosen Peneliti Ilmu Keislaman dan Sosial, 2022)
This study aims to review emotional intelligence and kalbu intelligence with a tasawuf (Sufism) approach in order to realize moderate religiosity. This is motivated by the religious phenomenon of some people or groups who often carry out anarchic actions against others under the pretext of